2021
DOI: 10.1253/circrep.cr-21-0006
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Door-to-Balloon Time and 30-Day Mortality According to Symptom Presentation in Patients With Acute Myocardial Infarction

Abstract: Background: We hypothesized that symptom presentation in patients with acute myocardial infarction (AMI) may affect their management and subsequent outcome. Methods and Results: Using Rural AMI Registry data, 1,337 consecutive patients with AMI who underwent percutaneous coronary intervention were analyzed. Typical symptoms were defined as any symptoms of chest pain or pressure due to myocardial ischemia. We considered the specific symptoms of dyspnea, nausea, or vomiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…[3][4][5] The 30-day mortality among MI patients presenting without chest pain have been estimated to 7-31%, whereas the equivalent mortality among chest pain MI patients was 2-9%. 3,29,33 A similar pattern was found for long-term mortality where the 1-year mortality was estimated to 4-17% and 15-23% in MI patients with and without chest pain. 3,28,30 Overall, previous findings indicate that the mortality risk is two to three times higher among non-chest pain MI patients compared to chest pain patients.…”
Section: Symptom Presentation Of Myocardial Infarction and Associated...supporting
confidence: 68%
See 2 more Smart Citations
“…[3][4][5] The 30-day mortality among MI patients presenting without chest pain have been estimated to 7-31%, whereas the equivalent mortality among chest pain MI patients was 2-9%. 3,29,33 A similar pattern was found for long-term mortality where the 1-year mortality was estimated to 4-17% and 15-23% in MI patients with and without chest pain. 3,28,30 Overall, previous findings indicate that the mortality risk is two to three times higher among non-chest pain MI patients compared to chest pain patients.…”
Section: Symptom Presentation Of Myocardial Infarction and Associated...supporting
confidence: 68%
“…2,5,9,[26][27][28] The literature suggests that the prevalence of MI patients presenting without chest pain is between 8% and 44% depending on the selection of MI patients. 1,2,4,[29][30][31][32][33] Previous studies have indicated that symptom presentation varies according to type of MI, where absence of chest pain have been found more common for NSTEMI, where 23% to 44% presented without chest pain, 4,28,30 whereas symptom presentation without chest pain among STEMI patients is somewhat less common (13% and 27%). 4,29,31 Advancement in treatment during the past decades has contributed to a considerable reduction in mortality after MI.…”
Section: Symptom Presentation Of Myocardial Infarction and Associated...mentioning
confidence: 99%
See 1 more Smart Citation
“…Patients misinterpreting MI symptoms, such as atypical symptoms, which are sometimes similar to COVID-19-related symptoms, might have interfered with an early diagnosis of an MI by choosing home recuperation [ 15 ]. In general, atypical symptoms in MI patients are reported to have a longer time-to-admission and reperfusion, and higher short-term mortality [ 14 , 23 ]. However, in the present study, there was no significant difference in the rate of symptom presentation and STATs in the NSTEMI patients between the after-pandemic period and pre-pandemic period, which might result in no difference in the 180-day mortality between the two time periods.…”
Section: Discussionmentioning
confidence: 99%
“…Typical symptoms were defined as any symptoms of chest pain or pressure with/without radiating to the arm, shoulder, neck, or jaw. Atypical symptoms were defined as any symptoms due to myocardial ischemia other than typical symptoms, including shortness of breath, nausea, abdominal pain, and loss of consciousness [ 14 ]. If the patients had a cardiopulmonary arrest at admission, it was defined as an OHCA.…”
Section: Methodsmentioning
confidence: 99%